THE ISOLATION OF PROTEIN FROM LATEX Hevea brasiliensis AND THE DETERMINATION OF CORROSION INHIBITION ACTIVITY TOWARD CARBON STEEL - ZAIN (NIM: 20507092), UFAIZAH
Carbon steel pipelines have been used to transport materials or product in industry. Petroleum industry is among the industries that utilized carbon steel pipelines. The presence of gasses such as CO2, O2 and H2S, as well as water in its environment, caused the corrosion towards the pipelines. Corrosion might occur at either inside or outside of the pipe. Corrosion which occurred at the outside parts of pipelines can be prevented by either coating or galvanic cell. On the other hand, corrosion which occurred at the inside parts of pipelines can be prevented by adding a corrosion inhibitor to its environment. Corrosion inhibitor can be defined as a chemical compound when added in small concentration to its environment would prevent or slow down corrosion rate. Corrosion inhibitors involve either inorganic or heteroatom organic compounds. Inorganic compounds such as chromates, phosphates and nitrites have not been used any longer because these compounds are toxic and can not be degraded in the earth that polluted environment. On the contrary, organic compounds is easier to be degraded and more environmental friendly. One of the organic compounds used as corrosion inhibitor is amino acid. Some research showed that amino acids such as proline, histidine and alanine, gave significant corrosion inhibition activity. The research also showed that amino acids which form peptide compounds gave better corrosion inhibition effect than single amino acid. Protein, which is amino acids polymer, is assumed to have comparable corrosion inhibition effect as much as amino acid and the peptide compounds. Latex, which is an extract isolated from rubber tree Hevea brasiliensis, has high economic value. Latex can be obtained by tapping the bark of rubber tree. Latex consisted of rubber particles and non rubber particles such as protein. However, in latex processing industry, the protein is not used and treated as waste because it can cause allergy to humans. The aim of this research is to utilize this protein as source of corrosion inhibitor towards carbon steel and therefore would enhance the economic value of protein latex.